ANALISIS KEBIJAKAN : STANDAR NASIONAL PENDIDIKAN, KURIKULUM MERDEKA DAN REGULASI PAI LAIN (KURIKULUM CINTA DAN ECO-TEHEOLOGI): Integration of National Education Standards, Independent Curriculum, Love Curriculum, and Eco-Theology - Adun Rahman; Dede Sudrajat; Ceceng Saepulmilah; Diansyah Permana; Gilang Muhamad Fajri Faresi (Journal of Research and Thought on Islamic Education (JRTIE), 2026)
This study analyzes education policy in Indonesia, focusing on the National Education Standards, the Independent Curriculum, and two innovative approaches to Islamic Religious Education, as: the Love Curriculum and Eco-Theology. The study was conducted through qualitative, library-based research, utilizing primary sources in the form of official regulations, policy documents, and educational guidelines, as well as secondary sources in the form of academic literature and previous research findings. The research findings indicate that the National Education Standards serves as a normative framework that provides boundaries, direction, and quality assurance for national education. Meanwhile, the Independent Curriculum serves as an implementation instrument that offers flexibility, learning differentiation, and pedagogical freedom for educational units and teachers. Conversely, the Love Curriculum presents an affective approach that fosters empathy, noble character, and humanistic pedagogical relationships. The Eco-Theology approach adds a spiritual-ecological dimension to Islamic Religious Education learning, so that students not only understand religious teachings but also internalize responsibility for environmental sustainability. The integration of these four components enables the realization of a comprehensive Islamic education model: promoting academic achievement, building character based on love and humanitarian values, while simultaneously fostering ecological awareness. Several previous studies on schools and madrasahs indicate that the success of policy implementation is greatly influenced by teacher competence, institutional support, and community involvement. Therefore, this research confirms that the future of Islamic Religious Education in Indonesia needs to be directed toward an integrative model that combines formal regulations, curriculum flexibility, values ​​of compassion, and ecological ethics as the foundation for holistic educational development.